Homonota horrida (NCN): Habitat - Pelegrin, Nicolas (2020)
Homonota horrida is distributed in Argentina and Paraguay (Cacciali et al. 2018. Zoosyst. Evol. 94:147–161; Talbot 1978. J. Herpetol. 12:433–435). It is an endemic species to the Chaco ecoregion. In the Arid Chaco, it is considered a forest specialist, and it is associated with leaf litter and fallen logs (Cruz 1994. Cuad. Herpetol. 8:119–125; Pelegrin and Bucher 2010. J. Arid Environ. 74:368–372; Pelegrin and Bucher 2012. J. Arid Environ. 79:13–19; Pelegrin and Bucher 2015. J. Nat. Hist. 49:2693–2708)...